Towards Relational Conceptions of Space in Education for Sustainable Development - Jekel, Thomas (Journal of Geography Education, 2008)
The debate of environmental education and education for sustainable development so far has largely missed out on the discussion of concepts of space used in teaching. This paper studies the consequences of the use of different concepts of space in education for sustainability, drawing on a differentiation of teaching and human interests. It proposes an inclusion of the concept of relational space in environmental education. This concept is thought to be compatible with action theory, emancipatory approaches of pedagogics and constructivist didactics.